Prospecção tecnológica em base de patentes: análise de tendências de tecnologias que empregam a radiação solar para produção de energia - Michielin Filho, Luis (2020)
The increased concern for the environment, coupled with the high cost of fossil fuels makes humanity look for new means of generating energy, different from traditional methods using non-renewable sources. The way found is through renewable sources, in which is the energy generated by the solar radiation that comes towards the Earth's surface, and can be used in several ways. One of the ways of visualizing which technologies are being used the most is by analyzing trends in technologies that employ solar radiation, which can be performed through technological prospecting on the basis of patents. The objective of this work is to identify which renewable technologies that use solar radiation as a source for energy production are generating more patent deposits, also identifying which countries receive more deposits of this type of technology, in addition to which companies publish more patents in the world. For this purpose, the Questel Orbit portal was used, and the years 2014 to 2018 were analyzed. At first it was identified that photovoltaic technology is the most used, and the country that receives the most deposits of renewable technologies is China. At world, the companies that most deposit patents related to the generation of energy through renewable resources are the multinationals General Electric, LG Electronics, Merck and Abengoa Solar.